Mitochondrial Transplantation Promotes Remyelination and Long-Term Locomotion Recovery following Cerebral Ischemia - Tao Chen; Yuanyuan Zhu; Jia Jia; Han Meng; Chao Xu; Panpan Xian; Zijie Li; Zhengang Tang; Yin Wu; Yan Liu (Hindawi Limited, 2022)
Cerebral ischemia usually leads to axonal degeneration and demyelination in the adjacent white matter. Promoting remyelination still remains a challenging issue in the field. Considering that ischemia deprives energy supply to neural cells and high metabolic activities are required by oligodendrocyte progenitor cells (OPCs) for myelin formation, we assessed the effects of transplanting exogenous healthy mitochondria on the degenerating process of oligodendrocytes following focal cerebral ischemia in the present study. Our results showed that exogenous mitochondria could efficiently restore the overall mitochondrial function and be effectively internalized by OPCs in the ischemic cortex. In comparison with control cortex, there were significantly less apoptotic and more proliferative OPCs in mitochondria-treated cortex. More importantly, higher levels of myelin basic protein (MBP) and more morphologically normal myelin-wrapped axons were observed in mitochondria-treated cortex at 21 days postinjury, as revealed by light and electron microscope. Behavior assay showed better locomotion recovery in mitochondria-treated mice. Further analysis showed that olig2 and lipid synthesis signaling were significantly increased in mitochondria-treated cortex. In together, our data illustrated an antidegenerating and myelination-promoting effect of exogenous mitochondria, indicating mitochondria transplantation as a potentially valuable treatment for ischemic stroke.